Rattus blangorum G. S. Miller 1942 ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
678. Aceh Rat Rattus blangorum French: Rat de Blangnanga / German: Aceh-Ratte / Spanish: Rata de Aceh Taxonomy. Rattus blangorum G. S. Miller, 1942, near Blangnanga Base Camp, 3600 feet (= 1097 m), Aceh foothills of Gunung Leuser, northern Sumatra, Indonesia. Phylogenetic position of R. blangorum in Rattus is currently unknown, although it is morphologically similar to R. tiomanicus, in which it was formerly included (separated based on multivariant morphological data). Monotypic. Distribution. Known only from type locality in N Sumatra. Descriptive notes. Head-body 139-149 mm, tail 161-175 mm, ear 16-18 mm, hindfoot 32-32-5 mm; weight 73-7-90-7 g. The Aceh Rat is small and similar to the Malaysian Field Rat (R. tiomanicus). Pelage is long and soft. Dorsum is yellowish ocherous buff. Venteris light grayish cream buff, with darker ocherous buff strip on chest. Feet are covered with silvery hair dorsally. Tail is ¢.116% of head-body length and dark blackish brown. Skull is smaller than that of the Malaysian ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Muridae, pp. 536-884 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 836, DOI: 10.5281/zenodo.6887260 ...